Process of inspecting road bridges in Ho Chi Minh City - Part 1: Existing inadequacies in the current process - Thanh, Nguyen Quang; Ba Tu, Vu; Hoai Bac, Nguyen; Dang Quang, Nguyen; Anh Tuan, Nguyen; Tien Thuy, Nguyen (Tạp chí Khoa học Công nghệ Giao Thông Vận Tải, 2022)
Quality inspection of traffic works, including quality control of simple bridge construction, is always a big problem in the management process of current authorities. This article will evaluate the outstanding issues in this current demand test standard, in which the study will build an overview evaluation model of the demand test standard and identify the outstanding shortcomings. The analysis from the article shows that the inspection process has problems that need to be supplemented and improved to both meet the requirements according to the process and properly represent the scientific nature of the problem. In addition, the inspection standards need to strongly eliminate problems that are not really necessary or that do not affect the quality of the work at the time of the survey. The issues investigated from the testing standards in the following sections include: remaining shortcomings in the existing bridge testing process; necessary additions in the bridge inspection process based on the development of science and technology; the bridge health monitoring system has been bringing about important decisions in assessing the quality of the bridge construction; the existing demand testing process – how to better match the rate of change of the present.